The torture camp on paradise street - Aseev, Stanislav, 1989- (Harvard library of Ukrainian literature, 2023)
In the memoir The Torture Camp on Paradise Street, Ukrainian journalist and writer Stanislav Aseyev details his experience as a prisoner for nearly three years at a modern-day concentration camp overseen by the Federal Security Bureau of the Russian Federation (FSB) in the Russian-controlled city of Donetsk.